Performance Comparison of Data Transfer on Windows Server and Linux Server Over IPv6 - Louangvilay, Xaythavy; Khieovongphachanh, Vimontha; Bounady, Khamphet (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
In today's world, modern technology systems play a significant role in development across various aspects globally. Multiple operating systems are widely used, such as Windows, Linux, and macOS, each supporting IPv6 functionality. This research focuses on studying data transfer performance between Windows Server and Linux Server using IPv6 connectivity with two main objectives: 1) to study data transfer between Windows Server and Linux Server via IPv6 connection, and 2) to examine resource usage between both servers. The experiment involved creating a physical network connected through a switch and installing FTP Server on both Windows Server and Linux Server operating systems in VMware ESXi on a Huawei RH2288H V3 server, configured with IPv6. FileZilla Client 3.84.1 was used for data transmission to compare Upload/Download speed performance and resource usage including CPU and RAM. The experimental results showed that Linux Server consistently outperformed Windows Server in transfer speeds. For text files: 1GB uploads were 8.16% faster on Linux (downloads showed no difference), 5GB uploads were 7.00% faster (downloads 3.10% faster), and 10GB uploads were 8.94% faster (downloads 2.41% faster). For audio files: 1GB uploads were 11.29% faster (downloads 4.35% faster), 5GB uploads were 9.28% faster (downloads 7.67% faster), and 10GB uploads were 7.23% faster (downloads 2.44% faster). For video files: 1GB uploads were 7.41% faster (downloads showed no difference), 5GB uploads were 9.42% faster (downloads 1.84% faster), and 10GB uploads were 11.59% faster (downloads 1.98% faster). Regarding resource usage, both systems showed identical CPU and RAM consumption for 1GB files across all types. However, for larger files, Linux demonstrated superior efficiency: 5GB files used 0.60-1.00% less CPU and 50-90MB less RAM, while 10GB files used 1.60-2.20% less CPU and 150-190MB less RAM depending on file type. In conclusion, Linux Server demonstrated faster transfer speeds and lower resource consumption compared to Windows Server.